Improved Connectivity Aware Geographical Routing Protocol in VANETs - Priyanga, D.; Sundararajan, T.V.P. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In recent years, rapid growth in the number of vehicles on the road has increased demands for communication. The design of routing protocols in VANETs is an important and necessary issue for supporting VANET-based applications. However, due to link disconnection, high mobility and uneven distribution of vehicles, it has been considered as a challenging issue to establish a robust route for delivering packets between source vehicles to destination vehicle. This paper presents an improved connectivity-aware intersection based routing (ICAIR) protocol to address these problems by selecting an optimal route with higher probability of connectivity and lower end to end delay; then, location forwarding based on position prediction is used to transfer packets among any three intersections along the best route. In simulation result, the proposed protocol outperforms existing routing protocols in terms of throughput and average transmission delay in an urban environment.